2021
DOI: 10.1177/0363546520986999
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Fixation for Distal Biceps Tendon Repairs: A Systematic Review and Meta-regression of Cadaveric Biomechanical Testing

Abstract: Background: Various surgical techniques can be used to repair acute distal biceps tendon (DBT) tears; however, it is unknown which type of repair or implant has the greatest biomechanical strength and presents the lowest risk of type 2 failure. Purpose: To identify associations between the type of implant or construct used and the biomechanical performance of DBT repairs in a review of human cadaveric studies. Study Design: Systematic review and meta-regression. Methods: We systematically searched the EMBASE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Biomechanical studies have shown adequate repair of using transosseous sutures, suture anchors, and suture buttons in a variety of pathologies, including distal biceps and pectoralis major repair. 9 , 14 , 15 , 16 , 17 , 18 The senior author began using the cortical button because of its improved control during the tensioning of the LUCL repair, aiming to provide anatomic fixation and prevent postoperative instability. The allowance for free sliding with the suture button permits minor adjustments in tension and, ultimately, a more anatomic repair.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies have shown adequate repair of using transosseous sutures, suture anchors, and suture buttons in a variety of pathologies, including distal biceps and pectoralis major repair. 9 , 14 , 15 , 16 , 17 , 18 The senior author began using the cortical button because of its improved control during the tensioning of the LUCL repair, aiming to provide anatomic fixation and prevent postoperative instability. The allowance for free sliding with the suture button permits minor adjustments in tension and, ultimately, a more anatomic repair.…”
Section: Discussionmentioning
confidence: 99%
“…The extracortical SB repair technique is widely considered to be biomechanically superior to other techniques owing to its superior tensile load. 28,40,42 Besides the fact that the extracortical SB repair technique did not reveal superior fixation strength as compared with the anatomic DB technique, extramedullary button fixation has demonstrated an increase in rates of intraoperative posterior interosseous nerve complications. 11,26,30 This has driven more anatomic and less dangerous techniques, such as intracortical fixation, to eliminate the requirement for far cortex drilling and button stabilization, thus minimizing posterior interosseous nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the tendon-to-bone fixation technique, a cortical-button fixation has been shown to be associated with greater mechanical strength and load to failure than other methods [ 19 ]. Camp et al described the surgical fixation of the acute distal biceps tendon rupture using a single intramedullary cortical-button with the advantages of minimizing the amount of native bone sacrifice and absence of violation of the far cortex, thereby reducing the risk of fracture [ 20 ].…”
Section: Discussionmentioning
confidence: 99%